A Challenging Case of Metastatic Intra-Abdominal Synovial Sarcoma with Unusual Immunophenotype and Its Differential Diagnosis - Yi-Che Changchien; Uhrin Katalin; János Fillinger; László Fónyad; Gergő Papp; Ferenc Salamon; Zoltán Sápi (Case Reports in Pathology)
The primary and metastatic gastrointestinal synovial sarcoma is rare with a wide differential diagnosis. It usually expresses cytokeratins EMA, BCL2 with an occasional CD99, and S100 positivity but not desmin. We present a case of metastatic synovial sarcoma with unusual immunophenotype causing diagnostic challenges. The tumor cells showed focal cytokeratin, EMA, and, unexpectedly, desmin positivity. Additional intranuclear TLE-1 positivity and negativity for CD34 and DOG-1 were also identified. A diagnosis of monophasic synovial sarcoma was confirmed by using FISH break-apart probe. RT-PCR revealed the SYT-SSX1 fusion gene. Intra-abdominal synovial sarcoma, either primary or metastatic, with unusual desmin positivity raises the diagnostic challenge, since a wide range of differential diagnoses could show a similar immunophenotype (leiomyosarcoma, desmoid tumor, myofibroblastic tumor, and rarely GIST etc.). Typical morphology and focal cytokeratin/EMA positivity should alert to this tumor, and FISH and RT-PCR remain the gold standard for the confirmation.